STUDY ON DETERMINATION OF CATCH FISH AREA USING DISTRIBUTION PARAMETERS OF SEA SURFACE TEMPERATURE AND DISTRIBUTION OF CHLOROPHYLL-A AT MAHAKAM DELTA MARINE - Suparjo, Suparjo; Beze, Husmul; Insanu, Radik Khairil; Arifin, Dawamul (Departemen Teknik Geomatika ITS, 2016)
As a maritime country , Indonesia has a comparative advantage in fisheries and marine resource potential . In 2010, the result of fish catches in Samarinda reached 9266.7 tons. Distribution of sea surface temperature and distribution of chlorophyll-a in the Mahakam Delta area required for mapping analysis of fishing grounds in order to maximize the potential of fish catches. The analysis using MODIS Terra satellite image with ATBD 19 MODIS algorithm to determine the concentration of chlorophyll -a and 25 MODIS ATBD algorithm to determine the sea surface temperature in the area of research. The Results of image data processing, sea surface temperatures in 2013 , 2014 and 2015 is dominated with temperatures ranging between 24°C to 28°C. In 2013 , the distribution of chlorophyll-a spread evenly. In 2014 , the waters were relatively less fertile due to the distribution of chlorophyll-a, identified less evenly. By 2015 , the waters were also less fertile. Chlorophyll-a was identified only slightly. Zone of fishing ground, in 2013, the distribution of many fish catches prediction zones spread along the coast north of the Mahakam Delta, the middle of Mahakam Delta and the middle of the Strait of Makassar.Distribution of little fish catches prediction zone were in the South Mahakam Delta. In 2014 , the many fish catches zone spread in the middle of Mahakam Delta and the little fish catches zone spread in north and south coast of the Mahakam Delta.In 2015, there were no many fish catches zones, just the little fish catches was indentified. The little fish catches zone spread in north and south coast of the Mahakam Delta.